2011
DOI: 10.4236/gsc.2011.13008
|View full text |Cite
|
Sign up to set email alerts
|

Degradation and Detoxification of Banana Postharvest Treatment Water Using Advanced Oxidation Techniques

Abstract: The elimination and detoxification of water contaminated with the principal commercial fungicides-thiabendazole (Textar 60 T) and imazalil sulphate (Fruitgard IS 7.5)-used in the postharvest treatment of bananas was successfully achieved through the use of advanced oxidation processes (AOPs). The techniques tested were heterogeneous photocatalysis with TiO 2 and TiO 2 -activated carbon (TiO 2 -CA) and Fenton and photo-Fenton processes. The evolution of fungicide concentration during degradation was studied tog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The capacity of the consortium to degrade TBZ at acidic conditions (pH 4.5) is against the general trend for inhibition of pesticide biodegradation by soil bacteria observed for other compounds such as chlorpyrifos, cinosulfuron and cypermethrin at pH equal or lower than 5.0 (Singh et al 2003;Ruan et al 2013;Yin et al 2013). However, its capacity to function under acidic conditions is a considerable advantage as wastewaters produced by citrus fruit-packaging plants contaminated with TBZ tend to be acidic (Santiago et al 2011). The consortium showed high degradation capacity in a range of temperatures (15-37°C) with an optimum between 26 and 37°C.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The capacity of the consortium to degrade TBZ at acidic conditions (pH 4.5) is against the general trend for inhibition of pesticide biodegradation by soil bacteria observed for other compounds such as chlorpyrifos, cinosulfuron and cypermethrin at pH equal or lower than 5.0 (Singh et al 2003;Ruan et al 2013;Yin et al 2013). However, its capacity to function under acidic conditions is a considerable advantage as wastewaters produced by citrus fruit-packaging plants contaminated with TBZ tend to be acidic (Santiago et al 2011). The consortium showed high degradation capacity in a range of temperatures (15-37°C) with an optimum between 26 and 37°C.…”
Section: Discussionmentioning
confidence: 96%
“…Its high application rates (up to 30 g L -1 for potato seeds and 0.25-2 g L -1 for fruits) (EC 2013b) result in the production of wastewaters contaminated with high TBZ levels. These effluents are considered hazardous according to the EC and they should be treated on site, before their final environmental discharge, to avoid detrimental effects on the biological and chemical quality of natural resources (EC 2001(EC , 2013aCastillo et al 2006;Santiago et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Those doses were calculated to represent a realistic loading scenario for a biobed system of 30 m 3 which receives in total 22 m 3 of wastewaters containing 10-15 mg l −1 of the pesticides studied. Such concentrations have been reported in recycled wastewaters from citrus fruit-packaging plants in Spain (Santiago et al, 2011). Pesticides were evenly mixed into the organic substrates and the moisture content was adjusted to 50% of their water holding capacity.…”
Section: Dissipation Of Pesticides In Organic Substratesmentioning
confidence: 99%
“…Postharvest treatments of fruits result in the production of large wastewater volumes which are characterized by low BOD/COD values but high concentrations of pesticides which should be detoxified prior to environmental release (Santiago et al, 2011). This need has been laid down on the registration documents of all relevant pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that photo-Fenton process is more efficient process which took 70 min for complete decolourization of dyes mixture; whereas 180 min were required for complete mineralization by Fenton reaction. Various AOPs techniques were employed by Santiago et al 57 for the degradation of commercial fungicides like thia-bendazole (Textar 60 T) and imazalil sulphate (Fruitgard IS 7.5) which are used in the post-harvest treatment of bananas. It was observed that Fenton process is the most efficient and low cost method for treatment of this type of water compared to heterogeneous photo catalysis with TiO 2 and TiO 2 -activated carbon (TiO 2 -CA) and photo-Fenton processes.…”
Section: Homogeneous Fenton and Photo-fenton Processesmentioning
confidence: 99%